1978
DOI: 10.1098/rsta.1978.0018
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of five thousand years of volcanism on Sao Miguel, Azores

Abstract: The activity of the three stratovolcanoes on the island of Sao Miguel is documented by tephrochronology, and during the past 5000 years a total of some 57 volcanic eruptions have taken place, mostly of magnitudes 4-6 on Tsuya’s scale. Approximately half were trachytic, and half basaltic. Each stratovolcano has a caldera within which each has had one historic eruption. The trachytic eruptions were predominantly explosive, and most took place from vents situated within the calderas. Isopach and isograde maps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(113 citation statements)
references
References 19 publications
(28 reference statements)
4
109
0
Order By: Relevance
“…Sa˜o Miguel, which is the largest island (757 km 2 ), has its geology dominated by the three active volcanoes of Sete Cidades, Fogo, and Furnas. Presenting fumarolic fields and hydrothermal vents (Booth et al, 1978;Cruz, 2003), and the always present ''rotten egg'' odor, the village of Furnas is built upon actively degassing ground inside Furnas caldera (Baxter et al, 1999), where the last eruption occurred at 1630 AD (Cole et al, 1995). Volcanic gases in this area are typically water vapor, carbon dioxide, H 2 S, SO 2 , with lesser amounts of other gases (Baxter et al, 1999;Ferreira and Oskarsson, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Sa˜o Miguel, which is the largest island (757 km 2 ), has its geology dominated by the three active volcanoes of Sete Cidades, Fogo, and Furnas. Presenting fumarolic fields and hydrothermal vents (Booth et al, 1978;Cruz, 2003), and the always present ''rotten egg'' odor, the village of Furnas is built upon actively degassing ground inside Furnas caldera (Baxter et al, 1999), where the last eruption occurred at 1630 AD (Cole et al, 1995). Volcanic gases in this area are typically water vapor, carbon dioxide, H 2 S, SO 2 , with lesser amounts of other gases (Baxter et al, 1999;Ferreira and Oskarsson, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Presenting fumarolic fields and hydrothermal vents (Booth et al, 1978;Cruz, 2003), and the always present "rotten egg" odor, the rural village of Furnas, in S. Miguel Island, is built upon actively degassing ground inside a volcanic caldera (Baxter et al, 1999), where the last eruption occurred at 1630 AD (Cole et al, 1995). This village has about 1541 inhabitants (Serviço Regional de Estatística dos Açores, 2003), where the age groups 0-14, 15-24, 25-44, 45-64, and over 64 represent 22%, 16%, 27%, 19%, and 16% of the local population, respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…The Furnas volcano has an older caldera of about 7 × 5 km and with a 290-m-depth depression, enclosing a younger caldera, with a diameter of approximately 5 km, where two subsidence events took place in the last 5,000 years (Guest et al, 1999). This explains the origin of the depressions where the Furnas village (Booth et al, 1978) and the Furnas lake are found today (Zbyszewski, 1961). The growth of the Furnas central volcano started about 100,000 years ago, mainly as a result of eruptions of trachytic pumice.…”
Section: Introductionmentioning
confidence: 90%
“…Their activity, throughout the last 5,000 years, is revealed by 57 volcanic eruptions, resulting in the production of over 4.6 km 3 of dense rock, and the current hydrothermal manifestations that occur mainly in the Fogo and Furnas volcanoes (Booth et al, 1978;Cruz, 2003). Furnas is the easternmost of the three active volcanoes on the island of São Miguel.…”
Section: Introductionmentioning
confidence: 99%